Business Project Management and Marketing Mastering Business Markets - Kleinaltenkamp, Michael; Plinke, Wulff; Geiger, Ingmar (Springer Texts in Business and Economics, 2016)
Marketing and implementing large-volume orders and major projects calls for specific types of expertise. This textbook deals with all of the management tasks involved: order management, inquiry evaluation and proposal preparation, pricing and revenue planning, order financing and financial engineering, contract management, negotiation management, project management, and finally project cooperation. Adopting a cross-sector perspective, it examines both traditional manufacturing industries and business-to-business services. All contributions are presented in an accessible style, making the book well-suited as both a managerial textbook and valuable practical guide. .